Wawasan Kebangsaan, Komitmen Negara, dan Nasionalisme dalam Pandangan Prof. Dr. KH Ali Mustafa Yaqub, MA - Nasrullah Nurdin (Jurnal Bimas Islam, 2018)
The fall of the New Order regime in 1998, which was followed by political leadership reform and democratization, opened the tap of many clogged thoughts. The various ideologies, identities, and interests that were previously pressed sprang to the surface and proclaimed its existence. Many people hope that with the fall of the New Order government, it has an impact on the reduced role of the State and strengthening the role of civil society. One of the functioning in civil society is the strong community institutions roles and non-governmental organizations in the religious, social, economic and cultural development of the State. In this regard, the role of Moslem scholars is also important in the post-collapse of the New Order. It Is Prof. Dr. KH Ali Mustafa Yaqub, MA, a few of the national religious figures who are quite vocal as well as concerned in expressing religious opinions, criticize the concepts that undermine the philosophy and ideology of the Unitary State of Republic of Indonesia (NKRI), as well as firm against the flow and defiance in this Republic. This paper attempts to trace his ideas about nationalism, the integrity of NKRI, state commitment, love of the homeland, the preservation of diversity, and his positive contribution to the development of a peaceful, harmony, safe and peaceful nation. Jatuhnya rezim Orde Baru pada tahun 1998, yang diikuti oleh reformasi kepemimpinan politik dan demokratisasi, membuka ketajaman pemikiran yang buntu. Berbagai ideologi, identitas, dan kepentingan yang sebelumnya ditekan muncul ke permukaan dan menyatakan eksistensinya. Banyak orang berharap bahwa dengan jatuhnya pemerintah Orde Baru, itu berdampak pada berkurangnya peran Negara dan memperkuat peran masyarakat sipil. Salah satu indikator dari fungsi masyarakat sipil adalah peran kuat lembaga masyarakat dan organisasi non-pemerintah dalam pembangunan agama, sosial, ekonomi dan budaya Negara. Dalam hal ini, peran Alim Ulama juga penting dalam pasca-runtuhnya Orde Baru. Adalah Prof. Dr. KH Ali Mustafa Yaqub, MA, beberapa tokoh agama nasional yang cukup vokal serta peduli dalam mengemukakan pendapat agama, mengkritisi konsep-konsep yang melemahkan falsafah dan ideologi Negara Kesatuan Republik Indonesia. (NKRI), serta tegas terhadap arus dan pembangkangan di Republik ini. Tulisan ini mencoba menelusuri ide-idenya tentang nasionalisme, integritas NKRI, komitmen negara, cinta tanah air, pelestarian keanekaragaman, dan kontribusi positifnya bagi pembangunan negara yang damai, harmonis, aman dan damai.